Occurrence of microcystins, anabaenopeptins and other cyanotoxins in fish from a freshwater wildlife reserve impacted by harmful cyanobacterial blooms. (30th April 2021) - Skafi, Mourad; Vo Duy, Sung; Munoz, Gabriel; Dinh, Quoc Tuc; Simon, Dana F.; Juneau, Philippe; Sauvé, Sébastien
Abstract: Harmful algal blooms of cyanobacteria (CyanoHABs) can lead to the release of potent toxins that can seriously affect ecosystem integrity. Some freshwater watersheds are particularly at risk considering the threats to already imperiled wildlife. The consumption of tainted drinking water and contaminated food also raises concerns for human health. In the present study, a pilot survey was conducted in the riverine ecosystem of the Pike River Ecological Reserve (QC, Canada) near Missisquoi Bay, Lake Champlain. We examined the occurrence of multiclass cyanotoxins including 12 microcystins, anatoxins, cylindrospermopsin (CYN), anabaenopeptins (AP-A, AP-B), and cyanopeptolin-A in surface waters and wild-caught fish during the summer 2018. Out of the 18 targeted cyanotoxins, 14 were detected in bloom-impacted surface water samples; toxins peaked during early-mid September with the highest concentrations for MC-LR (3.8 μg L −1 ) and MC-RR (2.9 μg L −1 ). Among the 71 field-collected fish from 10 species, 30% had positive detections to at least one cyanotoxin. In positive samples, concentration ranges in fish muscle were as follows for summed microcystins (∑MCs: 0.16–9.2 μg kg −1 ), CYN (46–75 μg kg −1 ), AP-A (1.1–5.4 μg kg −1 ), and AP-B (0.12–5.0 μg kg −1 ). To the best of our knowledge, this is one the first reports of anabaenopeptins occurrence in wildlife. The maximum ∑MCs in fish was 1.15-fold higher than the World Health Organization (WHO) daily intake recommendation for adults and nearly equated the derived value for young children. The concentration of CYN was also about 3-fold higher than the limit derived from the human health guideline values. Graphical abstract: Image 1 Highlights: The occurrence of 18 cyanotoxins was studied in a freshwater ecosystem (QC, Canada). MC-LR and MC-RR were predominant in HAB-impacted surface water. Anabaenopeptins (AP-A, AP-B) were detected across several fish species. MCs exceeded the WHO guideline (TDI = 0.04 μg kg −1 ) in some fish muscle samples. Samples from the study area containing MC and CYN may pose a risk to human health.